Tipificación de parásitos gastrointestinales en cánidos mediante pruebas de flotación y sedimentación a su ingreso en refugios de los valles de Quito - Escobar Maridueña, Sara Alejandra (2017)
The research sought the tipification and identification of gastrointestinal parasites in dogs, through the collection of fecal samples obtained at the time of their entry to the six different refuges of the Chillos and Tumbaco valleys in Quito. The 97 fecal samples of collected canids were analyzed using Koffoyd and Barber flotation and sedimentation techniques, and modified Sheater (Saturated Glucose Solution Method), in order to establish the presence of protozoa, Cestodes and nematodes, and to correlate their prevalence with variables associated with animals. The results that the reliability is high according to the size of the sample, show a prevalence of gastrointestinal parasites of 92.78% in the canines; and the identification of the most common parasites were Toxocara canis (61.86%), Dipylidium caninum (25,77%), Giardia canis (11,34%), Taenia spp (11,34%) and Isospora canis (1,03%). Additionally, Pearson's correlation is determined with a higher level confidence, higher than 0.99, which determines that the parasite prevalence is not related to the place of abandonment, size, gender and / or body condition of the animal. By the level of prevalence of parasitosis found in the analysis of canine affects, the null hypothesis is rejected and it is concluded that there is presence of gastrointestinal parasites in the feces of the canines admitted to the refuges. Key words: Canids, gastrointestinal parasites, shelters canids.